An experimental investigation into the soot particle emissions at early injection timings in a single-cylinder research diesel engine. (15th May 2022) - Wang, Yifeng; Zhuang, Yuan; Yao, Minfa; Qin, Yanzhou; Zheng, Zhunqin
Highlights: Effect of Early-injection on smoke emissions and engine performance were examined. Soot emission at early injection timings was reduced using highly volatile fuels. As the injection timing was advanced, more loose soot aggregates were produced. The RCCI mode is an effect method to reduce soot emissions at early injection timing. Abstract: Engine experiments were performed to examine the effect of early-injection on smoke emissions and engine performance under typical low temperature combustion (LTC) and reactivity controlled compression ignition (RCCI) operating conditions. On that basis, the influence of exhaust gas recirculation (EGR), intake pressure, fuel properties and fuel injection strategy on the engine-out soot emissions at early injection timings was also assessed. At last, the morphology, nanostructure characteristics of exhaust soot particles were analyzed. The test results showed when the injection timing was advanced before −30° crank angle after top dead center (CA ATDC) and earlier, the fuel spray impinged onto the piston crown surface, and a part of fuel entered into the squish zone and expanded to reach the cylinder liner wall and entered into the crevice volume, leading to a continuous increase in soot emissions, the peak smoke emission was found to occur at −55° CA ATDC. By adopting fuels with high volatilities and a RCCI fuel delivery strategy, soot emissions can be effectively reduced at early timings. Most of the high-resolution transmission electron microscopy (HRTEM) images of the sampled soot particles showed small spherical particles with a wide range of size distribution connected, and "onion-like" fringe arrangement was found in most of the images. As the fuel injection timing was retarded from −55° to −35° CA ATDC, the samples exhibited more highly organized carbon nanostructures; the fringe tortuosity and separation distance increased, while the fringe length decreased. The formation of more ordered arrangement of graphene layers led to significant resistance to oxidation.